Multifaceted Ultrafast Intramolecular Charge Transfer Dynamics of 4‑(Dimethylamino)benzonitrile (DMABN) - Park, Myeongkee; Kim, Chul Hoon; Joo, Taiha (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2013)
Intramolecular charge transfer (ICT) of DMABN has been the subject of extensive investigations. Through the measurements of highly time-resolved fluorescence spectra (TRFS) over the whole emission region, we have examined the ICT dynamics of DMABN in acetonitrile free from the solvation dynamics and vibronic relaxation. The ICT dynamics was found to be characterized by a broad range of time scales; nearly instantaneous (<30 fs), 160 fs, and 3.3 ps. TRFS revealed that an ICT state with partially twisted geometry, ICT(P), is formed within a few hundred femtoseconds either directly from the initial photoexcited state or via the locally excited (LE) state. The ICT(P) state undergoes further relaxation along the intramolecular nuclear coordinate to reach the twisted ICT (TICT) state with the time constant of 4.8 ps. A conformational diversity along the rotation of the dimethylamino group was speculated to account for the observed diffusive dynamics.